Novel Computerized Method for Automated Determination of Ventilatory Threshold and Respiratory Compensation Point - Kim, Kyoung Jae; Rivas, Eric; Prejean, Brian; Frisco, Dillon; Young, Millennia; Downs, Meghan (Frontiers in Physiology, 2021)
Introduction: The ventilatory threshold (named as VT1) and the respiratory compensation point (named as VT2) describe prominent changes of metabolic demand and exercise intensity domains during an incremental exercise test. Methods: A novel computerized method based on the optimization method was developed for automatically determining VT1 and VT2 from expired air during a progressive maximal exercise test. A total of 109 peak cycle tests were performed by members of the U.S. astronaut corps (74 males and 35 females). We compared the automatically determined VT1 and VT2 values against the visual subjective and independent analyses of 3 trained evaluators. We also characterized VT1 and VT2 and the respective absolute and relative work rates and distinguished differences between sexes. Results: The automated compared to the visual subjective values were analyzed for differences with t-test, for agreement with Bland-Altman plots, and for equivalence with a TOST (two one-sided test) approach. The results showed that the automated and visual subjective methods were statistically equivalent and the proposed approach reliably determined VT1 and VT2 values. Females had lower absolute O2 uptake, work rate, and ventilation, and relative O2 uptake at VT1 and VT2 compared to men (P≤0.04). VT1 and VT2 occurred at a greater relative percentage of their peak VO2 for females (67% and 88%) compared to males (55% and 74%) (main effect for sex: P<0.001). Overall, VT1 occurred at 58% of peak VO2, and VT2 occurred at 79% of peak VO2 (P<0.0001). Conclusion: Improvements in determining of VT1 and VT2 by automated analysis is time efficient, valid, and comparable to subjective visual analysis, and may provide valuable information in research and clinical practice as well as identifying exercise intensity domains of crewmembers in space.